PARTISIPASI MASYARAKAT DALAM PEMEKARAN DESA ATEP KECAMATAN LANGOWAN SELATAN - PALIT, SHERIF ARMANDO (JURNAL EKSEKUTIF, 2015)
Important of society participation him in the plan according to Conyers (1981:154-155) furthermore tell 3 especial reason why society participation in the plan have the nature of of vital importance : 1) Society participation represent an appliance utilize to obtain get information concerning condition, local society attitude and requirement 2) Society will be more trust program activity of development if them involved in preparation and its planning, because they will be more know the activity program the ins and outs and will have sense of belonging to activity program; and 3) Pushing public participation because will arise ascription that representing an rights democratize when society involved in development. Theory which is used in research participation concept, connective society concept in concept of Unfoldment at Countryside of Atep District of South Langowan. Research method the used is in perpective of approach qualitative (Moleong 2006:5) research qualitative is research using natural background, for the purpose of interpreteng phenomenon that happened and conducted by way of entangling various existing method. Â  Keyword : Participation, Society, Unfoldment